2020
DOI: 10.1109/access.2020.3006087
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Channel Estimation and Data Detection Based on Superimposed Training for Many Access MIMO System in Uplink

Abstract: Massive Multiple Input Multiple Output (MIMO) has great potential to improve spectrum efficiency in the fifth generation (5G) wireless communication systems. However, the efficiency was disastrously reduced by the heavy burden of overhead for device detection and channel estimation of the large amount of small data packets in the uplink channel. In the paper, we proposed a novel transmission scheme by superposing the training symbols for active device detection and channel estimation on the data symbols in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In this case, in order to allow a worsening of less than 50% of the minimum MSE, the range of averaging values must befall within [4,16]. Then, in order to compute this optimum value in its allowed range, considering a perfect knowledge of the SNR, the relative speed between the UE and the BS must be v robust 2 [35, 350] km/h, which in terms of Doppler frequency is a range of f robust d 2 [0.9, 9.5] kHz; on the other hand, if there is a perfect knowledge of the Doppler frequency, the SNR range of possible mismatching extends to ⇢ robust SNR 2 [3,22] dB. Obviously, the presented model exhibits a high robustness since the ranges of tolerance to input imprecisions are very broad relative to the resultant MSE computation worsening.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, in order to allow a worsening of less than 50% of the minimum MSE, the range of averaging values must befall within [4,16]. Then, in order to compute this optimum value in its allowed range, considering a perfect knowledge of the SNR, the relative speed between the UE and the BS must be v robust 2 [35, 350] km/h, which in terms of Doppler frequency is a range of f robust d 2 [0.9, 9.5] kHz; on the other hand, if there is a perfect knowledge of the Doppler frequency, the SNR range of possible mismatching extends to ⇢ robust SNR 2 [3,22] dB. Obviously, the presented model exhibits a high robustness since the ranges of tolerance to input imprecisions are very broad relative to the resultant MSE computation worsening.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…• opt will not be discussed and the common defined values by academia will be employed ( = 0.2) [6], [11]- [13], [15], [22]. Usually, the optimization of requires further analysis related to the throughput which is not covered in this paper.…”
Section: Mse Optimization Via Time Averagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed method considers a decoupled optimization scheme between the RF and baseband domains for the SE maximization problem. In [8], the authors developed a novel transmission scheme by superposing the training symbols for active device detection and channel estimation on the data symbols in the uplink transmission to mitigate the cross interference among the superposed signals and improve the efficiency. In [9], the authors showed that cognitive spectrum sensing and power harvesting can be accomplished simultaneously.…”
Section: Introductionmentioning
confidence: 99%